Violenţa asupra femeii în familie - Bonea, Georgiana Virginia (Calitatea Vieții, 2016)
The main objective of this paper is to highlight and analyze issues related to violence against women within the family. “The main cell of society”, as it is called, family is the first environment in which the individual forms (family home), and on the other hand, becomes a way of rebuilding a new life through marriage or domestic partnership. Thus, the negative experiences that the individual has lived in his family of origin could have some implications in his present family life, as a parent and partner. In order to better analyze how violence against women in the family, have highlighted the theory called: “Violence cyclicality”, analyzed over time by the American researcher Lenore Walker. Through this theory, this paper will further clarify on the state of cyclic episodes of violence occurred between partners in intimate family life. There is also a large discrepancy between the statistics of the General Directorates for Social Assistance and Child Protection ‒ DGASPC and that of the Police, which will be discussed extensively.